Studi Kasus Bimba AIUEO: Analisis Sistem Pengelolaan Kas Pada Pendidikan Anak Usia Dini (PAUD) Berdasarkan Standar Akuntansi Keuangan - Safrizal, Safrizal; Khasanah, Shokhihatun (Balai Diklat Keagamaan Surabaya, 2024)
An educational foundation is a type of foundation established with the aim of providing education, both formal and non-formal. Early childhood education (PAUD) is the foundation of all education and plays a role in early childhood development. Financial Accounting Standards (SAK) are accounting standards that regulate all processes of creating, compiling, recording and presenting accounting information with the aim of making financial reports consistent and easy to understand by users. This research was conducted using qualitative methods, which are the results of interviews obtained by researchers from the BiMBA AIUEO Early Childhood Education (PAUD) manager, because this manager knows more about the preparation of cash flows and monthly transaction records. In this research, the data sources obtained are secondary data and other data in the form of institutional profiles, history, vision, mission and financial reports. From the results of the research that occurred regarding the implementation of the cash management system, namely that a good and correct accounting cycle has not been implemented and there has not been a cash management report prepared in accordance with Financial Accounting Standards (SAK) in BiMBA AIUEO Early Childhood Education (PAUD)